Anisotropic laser-pulse-induced magnetization dynamics in van der Waals magnet Fe3GeTe2. (1st January 2023) - Lichtenberg, Tom; Schippers, Casper F; van Kooten, Sjoerd C P; Evers, Stijn G F; Barcones, Beatriz; Guimarães, Marcos H D; Koopmans, Bert
Abstract: Femtosecond laser-pulse excitation provides an energy efficient and fast way to control magnetization at the nanoscale, providing great potential for ultrafast next-generation data manipulation and nonvolatile storage devices. Ferromagnetic van der Waals materials have garnered much attention over the past few years due to their low dimensionality, excellent magnetic properties, and large response to external stimuli. Nonetheless, their behaviour upon fs laser-pulse excitation remains largely unexplored. Here, we investigate the ultrafast magnetization dynamics of a thin flake of Fe3 GeTe2 (FGT) and extract its intrinsic magnetic properties using a microscopic framework. We find that our data is well described by our modeling, with FGT undergoing a slow two-step demagnetization, and we experimentally extract the spin-relaxation timescale as a function of temperature, magnetic field and excitation fluence. Our observations indicate a large spin-flip probability in agreement with a theoretically expected large spin–orbit coupling, as well as a weak interlayer exchange coupling. The spin-flip probability is found to increase when the magnetization is pulled away from its quantization axis, opening doors to an external control over the spins in this material. Our results provide a deeper understanding of the dynamics van der Waals materials upon fs laser-pulse excitation, paving the way towards two-dimensional materials-based ultrafast spintronics.